Praktik Permohonan Dispensasi Kawin di Pengadilan (Studi Peraturan Mahkamah Agung Nomor 5 Tahun 2019) - Rachmatulloh, Mochammad Agus; Syafiuddin, Chafidz (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2022)
The age of marriage for men and women is 19 years. If there is an age deviation, the marriage can only be carried out after obtaining a marriage dispensation from the court. There are many applications for dispensation from marriage in Indonesia, each year there is a significant increase. The reason that is often put forward is that the relationship between the prospective bride and groom is very close, parents are afraid that they will fall into acts that are contrary to religion. The number of cases is high and to anticipate disparities in the handling of cases, as well as the process of adjudicating has not been regulated in a clear and detailed manner, so that the administration of justice runs smoothly, the Chief Justice of the Supreme Court stipulates Supreme Court Regulation Number 5 of 2019 concerning Guidelines for Adjudicating Applications for Marriage Dispensation. In this regulation, there are new provisions that regulate the procedure for examining cases that are different from the previous one. It is important to know about child marriage through the mechanism for applying for a marriage dispensation, it is interesting to discuss how the practice of applying for a marriage dispensation is carried out in court. The study method used was a normative legal research method, with a statutory approach, and PMA primary legal materials Number 5 of 2019. The application for a marriage dispensation was based on urgent reasons, accompanied by supporting evidence and listening to all interested parties. The examining judge is a single judge, with the classification having a decision letter as a juvenile judge or other provisions. In the examination, judges and substitute clerks may not use trial attributes, use language and methods that are easy for children to understand and understand. The legal considerations that must be contained in the determination are that they have given advice and heard the statements of interested parties, otherwise the determination will be null and void. The decision was taken after careful and comprehensive consideration, still based on legal facts, and involving the child for whom dispensation was requested, based on the spirit of preventing child marriage. Everything is done in order to realize a fair determination for children and all interested parties.